Quark matter in a QCD Coulomb gauge quark model - Antunes, S. M. [UNESP]; Krein, Gastão Inácio [UNESP]; Vizcarra, V. E. [UNESP]; Panda, P. K. (Sociedade Brasileira de Física, 2005)
In this communication we present results of a study of chiral symmetry in quark matter using an effective Coulomb gauge QCD Hamiltonian. QCD in Coulomb gauge is convenient for a variational approach based on a quasiparticle picture for the transverse gluons, in which a confining Coulomb potential arises naturally. We show that such an effective Hamiltonian predicts chiral restoration at too low quark densities. Possible reasons for such deficiency are discussed.